2019
DOI: 10.1523/jneurosci.2289-18.2018
|View full text |Cite|
|
Sign up to set email alerts
|

Representation of Auditory Motion Directions and Sound Source Locations in the Human Planum Temporale

Abstract: The ability to compute the location and direction of sounds is a crucial perceptual skill to efficiently interact with dynamic environments. How the human brain implements spatial hearing is, however, poorly understood. In our study, we used fMRI to characterize the brain activity of male and female humans listening to sounds moving left, right, up, and down as well as static sounds. Whole-brain univariate results contrasting moving and static sounds varying in their location revealed a robust functional prefe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 111 publications
6
19
0
Order By: Relevance
“…Consistently with previous investigations (Fine et al, 2005;Finney et al, 2001;Sadato et al, 2005;Shiell et al, 2014), the present work confirms the recruitment of the superior temporal cortex in response to visual motion processing in early deaf individuals. Our study adds on these previous reports by showing that cross-modal visual motion processing is restricted to the portion of the right superior temporal cortex that is preferentially recruited by auditory motion in hearing individuals (Battal et al, 2019). Further, we observed that the visually reorganized STC of deaf people is capable of accurately discriminating between different categories of visual motion (i.e.…”
Section: Functional Responses For Visual Motion In Right Stc Of Deaf supporting
confidence: 79%
See 1 more Smart Citation
“…Consistently with previous investigations (Fine et al, 2005;Finney et al, 2001;Sadato et al, 2005;Shiell et al, 2014), the present work confirms the recruitment of the superior temporal cortex in response to visual motion processing in early deaf individuals. Our study adds on these previous reports by showing that cross-modal visual motion processing is restricted to the portion of the right superior temporal cortex that is preferentially recruited by auditory motion in hearing individuals (Battal et al, 2019). Further, we observed that the visually reorganized STC of deaf people is capable of accurately discriminating between different categories of visual motion (i.e.…”
Section: Functional Responses For Visual Motion In Right Stc Of Deaf supporting
confidence: 79%
“…Although cross-modal activation of auditory regions has been observed in response to visual motion in deaf humans (Fine et al, 2005; Finney et al, 2001; Shiell et al, 2014), several important questions remain unanswered. In our study we tested whether visual motion processing recruits discrete regions of the temporal cortex known to selectively respond to specific auditory motion trajectories in hearing individuals (Battal et al, 2019; Hall and Moore, 2003; Warren et al, 2002). In addition, we used multivariate pattern decoding analyses to assess whether different motion trajectories could be discriminated in the deprived auditory cortex of deaf people.…”
Section: Introductionmentioning
confidence: 99%
“…In the human auditory system, the planum temporale (hereafter hPT), which is located in the superior temporal cortex (posterior to Heschl’s gyrus), engages preferentially in the processing of moving sounds (Baumgart and Gaschler-Markefski, 1999; Warren, Zielinski and Green, 2002; Krumbholz et al ., 2005). Similar to what was found in hMT+/V5 for the processing of visual directions, hPT also codes for the direction of sounds following an axis-of-motion organization (Battal et al ., 2019).…”
Section: Introductionsupporting
confidence: 69%
“…According to one parcellation (Glasser et al 2016), electrode 2 was located on the border of the fundus of the superior temporal area FST and the putative human temporal area PHT. Interestingly, the latter was recently shown to code for auditory motion and source location (Battal et al 2019). Moreover, the electrode's visual pRF properties are in line with the localization of the electrode within TO2.…”
Section: Discussionmentioning
confidence: 56%
“…Even primary visual cortex has been shown to be involved in Braille reading by the visually impaired (Sadato et al 1996;Zangaladze et al 1999). Moreover, in the last decades several neuroimaging studies have reported auditory and tactile responses to motion stimuli in the human Middle Temporal complex hMT+, more specifically in the most anterior part of the complex, known as visual extrastriate area MST (Blake et al 2004;Van Boven et al 2005;Beauchamp et al 2007;Ricciardi et al 2007;Ptito et al 2009;Summers et al 2009;Sani et al 2010;Van Kemenade et al 2014) and also in the human planum temporale (Battal et al 2019). Other fMRI studies offer contradictory findings about the contribution of extrastriate cortex to tactile motion processing.…”
Section: Introductionmentioning
confidence: 99%